The line of the sun : a novel - Cofer, Judith Ortiz, 1952-2016 (Book collections on Project MUSE., 1989)
"Set in the 1950s and 1960s, The Line of the Sun moves from a rural Puerto Rican village to a tough immigrant housing project in New Jersey, telling the story of a Hispanic family's struggle to become part of a new culture without relinquishing the old. At the story's center is Guzmán, an almost mythic figure whose adventures and exile, salvation and return leave him a broken man but preserve his place in the heart and imagination of his niece, who is his secret biographer."--Provided by publisher